The Effect of Trust Benefit and Risk Perception of GM Foods on Behavior Intention: A Study on University Students - Erkan Arı; Veysel Yılmaz; Murat Olgun (Journal of Economy Culture and Society)
The aim of this study is to examine the attitudes and behaviors of university students towards “foods containing Genetically Modified Organisms” (GMO). For this purpose, firstly, a research model was proposed to describe the relationships between attitudes and behaviors towards GMO by making use of the literature review, and then various hypotheses were formed to test the relationships between the factors in the model. The factors in the proposed research model are “Attitude (ATT),”“Attitude towards Knowledge and Technology (KNOW),” “Trust (TRUST),” “Perceived Benefit (BEN),” “Perceived Risk (RISK)” and “Behavior (BEH)”. In the study, the proposed research model was analyzed using Structural Equation Modeling (SEM), and the suitability of the proposed model was evaluated according to various fit criteria. As a result of the analysis, it was determined that a one-unit increase in the perceived benefit and perceived risk for GMO will cause an increase of 0.89 units and a decrease of 0.19 units, respectively, in the attitude towards GMO. In addition, it was determined that as trust in scientific research results, media, labeling system and inspection systems increase, the perception that GMO can be beneficial will also increase.